2007
DOI: 10.1189/jlb.0807578
|View full text |Cite
|
Sign up to set email alerts
|

Injection of lipopolysaccharide induces the migration of splenic neutrophils to the T cell area of the white pulp: role of CD14 and CXC chemokines

Abstract: There is increasing evidence that neutrophils are involved in the regulation of adaptive immunity. We therefore tested whether these cells may colocalize with T lymphocytes in lymphoid organs. Our results demonstrate that administration of the microbial product LPS induces the migration of neutrophils in the spleen from the red pulp and the marginal zone to the area of the white pulp where T cells reside. This movement is CD14-dependent, whereas the recruitment of neutrophils in the peritoneal cavity is increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Expression of the lymph node homing receptor CCR7 by activated neutrophils was reported before (30) but could not be confirmed in the current study (data not shown). Still, APClike neutrophils may also gain access to inflamed draining lymph nodes through the action of inflammatory chemokines (7)(8)(9)(10). Irrespective of the anatomical context, APC-like neutrophils may contribute to protective immune responses, by fighting the "first hit" infection as a result of inducing Ag-specific CD4 + and CD8 + T cells and by harnessing the T cell compartment against potential "second hit" infections.…”
Section: Effector Cd4mentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the lymph node homing receptor CCR7 by activated neutrophils was reported before (30) but could not be confirmed in the current study (data not shown). Still, APClike neutrophils may also gain access to inflamed draining lymph nodes through the action of inflammatory chemokines (7)(8)(9)(10). Irrespective of the anatomical context, APC-like neutrophils may contribute to protective immune responses, by fighting the "first hit" infection as a result of inducing Ag-specific CD4 + and CD8 + T cells and by harnessing the T cell compartment against potential "second hit" infections.…”
Section: Effector Cd4mentioning
confidence: 99%
“…As such, neutrophils regulate the recruitment and function of various cell types and interact with immune and nonimmune cells. Intriguingly, neutrophils directly affect Ag-specific responses by facilitating monocyte differentiation and dendritic cell maturation, and by interacting with T cells and B cells (4)(5)(6)(7)(8)(9)(10). Murine neutrophils have been shown to present Ags to both CD4 + and CD8 + T cells (11)(12)(13), and to differentiate into neutrophil-dendritic cell hybrids in vitro and in vivo (14,15).…”
mentioning
confidence: 99%
“…Immunohistochemistry was performed as described previously (24). Briefly, spleens were fixed in ImmunoHistoFix (Aphase, Nassogne, Belgium), embedded in ImmunoHistoWax (Aphase), and sectioned at 3-6 mm.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…A possible reason is that long-term contact between noxious substances, such as endotoxin and hepatitis virus, and spleen tissue has promoted activation and hyperplasia of lymphocytes in the spleen [16,25] . Also, this contact has enhanced its function to maximize the elimination of toxins in the body and maintain body balance [26][27][28][29] .…”
mentioning
confidence: 99%